(untitled) (Texas Journal of Medical Science, 2022)
It is known that both lack and excess of motor activity are a pathogenetic factor leading to diseases. The body must choose the path of adaptation and glucocorticoid hormones help it in this, which includes cortisol, which is the main compound that ensures the development of a general adaptation syndrome. The article describes the possibility of using a non-invasive, accessible and informative rapid analysis of oral fluid, conducted according to a minimum number of indicators (ionized calcium, salivation volume, arterial pulse and respiratory rate), which makes it possible to assess the degree of physical activity of the child, to choose the optimal motor mode and, if necessary, to correct it.